Peran Pengalaman Membeli Terhadap Minat Pembelian Ulang dengan Mediator Sikap dan Kesadaran Ramah Lingkungan - Dina Febriana Anggraini; Albari Albari (Publikasi Indonesia, 2022)
This study aims to explain the effect of purchasing experience, environmental awareness and environmentally friendly attitudes on purchase intention using the object of Innisfree environmentally friendly skin care products. The increasing public demand for the use of natural ingredients and an environmentally friendly lifestyle goes hand in hand with public concern about harmful ingredients containing chemicals is also increasing, which is the reason skin care companies specifically serve the trend of using natural ingredients in order to strengthen their marketing strategy. The sample used in this study amounted to 166 respondents located in the territory of Indonesia. The technique used for sampling is convenience sampling. The analysis technique used is SEM analysis with the help of the AMOS 24 program. The hypothesis results show that there is a positive and significant influence on the variables of purchasing experience, environmental awareness, environmentally friendly attitudes, and purchase intention.